REACTIVE DIVIDING WALL COLUMN (RDWC) PADA PRODUKSI DIETIL KARBONAT - Devina Affriani Reyga Riswandi; Michelle Tanujaya; Yansen Hartanto; Herry Santoso (JURNAL INTEGRASI PROSES, 2019)
In this era, the needs for chemicals are increasing. One of them is an additive called diethyl carbonate that is produced by the transesterification reaction of dimethyl carbonate and ethanol. To produce diethyl carbonate by conventional distillation with high purity is expensive and requires a lot of energy, so that new breakthroughs and innovations are needed to overcome this problem. The new breakthrough and innovation proposed in this study is Reactive Dividing Wall Column (RDWC). The purpose of this study is to design an RDWC model and optimize the Reactive Dividing Wall Column. In this study, Aspen Plus software was used. The operating unit model used was RadFrac. The thermodynamic model used was the UNIQUAC model. Then using the literature on reactive distillation, the data were validated. After it was valid, the data will be used to design and optimize RDWC. Variables for optimization are: number of reactive trays, number of trays with a wall, total tray number, and DMC feed location. The results showed that RDWC for the production of diethyl carbonate produced a lower value of TAC than conventional methods. The TAC value obtained was 1,310,706,938 / year. The Reactive Dividing Wall Column design for optimum diethyl carbonate production has a total number of 24 reactive stages, a total number of 26 wall stages, 77 total stages and dimethyl carbonate feed locations on the 71st stage.